Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1159/000126974
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional Specific and Modulated Brain to Blood Transport of Corticotropin-Releasing Hormone

Abstract: Corticotropin-releasing hormone (CRH) is produced and acts both within the central nervous system and at several peripheral sites. However, it is not known whether CRH is able to cross the blood-brain barrier (BBB) in either direction, or whether the central and peripheral compartments are independent. We studied the transport across the BBB of both human/rat CRH (hCRH) and ovine CRH (oCRH) using the native peptides labeled with 125I at the histidine residue, thereby avoiding the use of other synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 32 publications
4
58
2
Order By: Relevance
“…Other studies of CRF infusion in young men have found either a decrease in delta sleep (Holsboer et al, 1988) or no effect on sleep (Born et al, 1989). Exogenous CRF does not cross the blood-brain barrier (Martins et al, 1996) but can Delta sleep response to metyrapone in PSTD TC Neylan et al affect periventricular structures, particularly the hypothalamus. Peripheral administration of CRH antagonists that do not cross the blood-brain barrier have been found to reduce spontaneous waking (Chang and Opp, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…Other studies of CRF infusion in young men have found either a decrease in delta sleep (Holsboer et al, 1988) or no effect on sleep (Born et al, 1989). Exogenous CRF does not cross the blood-brain barrier (Martins et al, 1996) but can Delta sleep response to metyrapone in PSTD TC Neylan et al affect periventricular structures, particularly the hypothalamus. Peripheral administration of CRH antagonists that do not cross the blood-brain barrier have been found to reduce spontaneous waking (Chang and Opp, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…It is also possible that the release of CRF stems from sources other than placenta. Studies in adult mice report the existence of specific unidirectional brain-to-blood transport system for CRF (34). Furthermore, this transport system is acutely modulated by adrenal steroids suggesting the participation in the control of stress response (35).…”
Section: Discussionmentioning
confidence: 99%
“…This effect is likely at the level of the pituitary outside of the blood-brain barrier, as peripherally administered hCRF has poor central penetrance (Martins et al, 1996). Whether this effect is also because of hCRF action in the hypothalamus is unknown.…”
Section: Discussionmentioning
confidence: 99%